2011
DOI: 10.1002/lary.22339
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective dental protection during rigid endoscopy

Abstract: We describe a simple method to create a reusable and customizable dental guard using readily available materials. Our method does not require an extra patient visit and does not add operative time. Furthermore, our guard is rigid, which allows force to be distributed over adjacent teeth, unlike soft mouth guards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Use of tooth protectors and mouth guards have been proposed to minimize dental injuries[ 15 , 30 - 32 ]. These function by dispersing force applied among the teeth to minimize overloading a damaged tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Use of tooth protectors and mouth guards have been proposed to minimize dental injuries[ 15 , 30 - 32 ]. These function by dispersing force applied among the teeth to minimize overloading a damaged tooth.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with prominent upper teeth, a 1-2 millimeter reduction in the inter incisor distance because of the teeth guard proposed by Talmon and Gilbey [6] can contribute to dif icult access and increases the risk of dental trauma. Formation and application of a thermoplastic mouthguard as suggested by Domanski, et al [7] spreads the laryngoscope-related pressure uniformly onto the teeth. We employ extending the teeth guard onto the hard palate which has helped us greatly to minimise dental trauma during rigid endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested the use of ‘boil and bite’ mouth guards; 5 however, this requires patient preparation and cost prior to surgery, and these may still not be suitable for edentulous patients. Others have suggested the use of nasal splints to use as mouth guards, 1 but there is no evidence regarding how well they reduce dental or oral mucosal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of rigid oesophagoscopy include perforation, mediastinitis, bleeding, dental injury and soft tissue injury. Although dental injuries are a well-recognised risk (most commonly, the maxillary incisors 1 ), the rates of injury reported in the literature are variable, ranging from 0.06 per cent 2 to 12 per cent. 3 Oral mucosa injuries are more common and have been found to occur in up to 75 per cent of patients.…”
Section: Introductionmentioning
confidence: 99%